A quantitative description of end‐plate currents - Karl L. Magleby; Charles F. Stevens (1972)
1. End-plate currents have been studied in glycerol-treated frog sartorius nerve-muscle preparations with the voltage clamp technique.2. The effects of temperature on the decay rate of end-plate currents were investigated over a temperature range from 10 to 30.5 degrees C. The Q(10) for the decay constant of end-plate currents depends somewhat on membrane potential; at - 100 mV the decay constant has a Q(10) of 2.7.3. Peak end-plate current depends non-linearly on membrane potential with a decreasing slope conductance associated with hyperpolarization.4. The ;instantaneous' voltage-current relationship for end-plate channels was determined by causing step changes in membrane potential during end-plate current flow. This relationship appears to be linear.5. The interaction of acetylcholine with its receptor is viewed as being analogous to the first step in enzymic catalysis. On this view, acetylcholine binds to its receptor and induces a conformational change which is responsible for opening end-plate channels. By analogy to the first steps in the catalytic sequence of enzymes, the binding step is very rapid, almost diffusion-limited, and the conformational change is rate-limiting.6. Equations describing this process have been derived. Expressions for the rate constants have also been derived by considering changing dipole moments of the transmitter-receptor complex associated with the conformational change. As the transmitter-receptor complex is in the membrane field, different conformational states have different energies, and the rate of conformational change thus depends on membrane potential. The equations thus derived are shown to account adequately for the time course of end-plate conductance change.